Impact of the COVID-19 pandemic on the work of social workers: - a comparison between Germany, Switzerland and the Netherlands (Journal of Comparative Social Work, 2022)
The COVID-19 pandemic has had a major impact on everyone’s life.  Like many other professionals, social workers have been forced to adapt to these new working conditions and new challenges in order to support clients during the pandemic, as new needs have arisen. Together with professional associations from three nations (Germany, Switzerland and the Netherlands), we used a coordinated approach to explore the consequences of the pandemic for social work professionals. This study was conducted during the most severe contact and hygiene restrictions of the second wave of the COVID-19 pandemic in the winter of 2020/2021. The data addresses the changes perceived by social work professionals in relation to their contact and communication with clients, the use of digital technology in the context of work, the professional response in terms of innovation, the working conditions and the psychosocial risks they face.MethodsCross-sectional data was collected from 7,241 social workers in Germany, Switzerland and the Netherlands through online surveys.ResultsThe results show an increase in the workload of professional social workers and compounding problems of clients, together with a negative impact of the COVID-19 pandemic on communication and contact with clients. All of this takes place within the framework of changing working conditions and contexts. Our data shows that the use of digital technologies does not cause bigger problems for most of the participating social workers. It should in fact be noted that professionals have many positive associations with the use of digital technology in general.ConclusionsThere are both remarkable and alarming results concerning the mental health of social workers and their working conditions, as well as the position of the social work profession in general.